Evaluation of the abamectin plus oxfendazole combination to control resistant nematodes in cattle - Cantón, Candela (2021)
The current study evaluated the efficacy and the potential pharmacokinetic(PK) interactions occurring after the oral administration of abamectin(ABA) and oxfendazole(OXF) given both separately and co-administered to calves in two farms(A and B). On each farm sixty(60) male calves infected with gastrointestinal nematodes were randomly allocated into four groups(n= 15): Control: animals did not receive anthelmintic treatment; ABA: treated with ABA(0.2 mg/kg); OXF: treated with OXF(4.5 mg/kg); ABA+OXF: simultaneously treated with ABA and OXF(at the above doses). Seven(7) animals from each treated group(from Farm B) were randomly selected to perform the PK study with blood samples being taken from these animals at regular intervals. A significantly(P<0.05) higher Cmax value was obtained for ABA alone(38.8±6.5 ng/mL), compared to that estimated after its co-administration with OXF(25.4±10.3ng ⁄mL). However, the ABA systemic exposure(expressed as AUC) obtained after administration of ABA alone(166±30.8 ng.d/mL) was similar to that observed in the ABA+OXF group(118±52.3 ng.d/mL). Likewise, OXF AUC values were similar after OXF administration alone(8.2±1.5 µg.h/mL) or combined with ABA(9.1±2.6 µg.h/mL). Overall, no adverse PK interactions were observed after the combined treatment. On Farm A, the Cooperia spp. were resistant to OXF, and the Ostertagia spp. were resistant to both ABA and OXF.Under this scenario the combined treatment only achieved an 84% efficacy against the multiple resistant Ostertagia spp.In contrast, on Farm B the Haemonchus spp. were resistant to ABA, the Ostertagia spp. were resistant to OXF and both anthelmintics failed to control the Cooperia spp.However, under the epidemiological conditions on Farm B, the combination was the only treatment that achieved 99.9% efficacy against all genera, indicating an additive effect of the combined treatment.Overall, an ABA+OXF combination can be useful to optimise the control of resistant gastrointestinal nematodes of cattle.However, its use must be necessarily supported by previous diagnosis of the resistant status of the nematode population.